The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1016/j.neuro.2008.04.008
|View full text |Cite
|
Sign up to set email alerts
|

Anti-cancer drug induced neurotoxicity and identification of Rho pathway signaling modulators as potential neuroprotectants

Abstract: Many chemotherapy drugs are known to cause significant clinical neurotoxicity, which can result in the early cessation of treatment. To identify and develop more effective means of neuroprotection it is important to understand the toxicity of these drugs at the molecular and cellular levels. In the present study, we examine the effects of paclitaxel (taxol), cisplatin, and methotrexate on primary rat neurons including hippocampal, cortical, and dorsal horn/dorsal root ganglion neuronal cultures. We found that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
54
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 64 publications
(54 citation statements)
references
References 52 publications
0
54
0
Order By: Relevance
“…Inhibitor compounds have been described for Rho kinase (ROCK) (8), an important downstream effector of RhoA, and peptide-derived ligands that target the p75 neurotrophin receptor upstream of RhoA have also been developed to modulate RhoA/ROCK activity (20). To date, however, there has been a lack of compounds directed at either RhoGEFs or RhoGAPs (28).…”
Section: Discussionmentioning
confidence: 99%
“…Inhibitor compounds have been described for Rho kinase (ROCK) (8), an important downstream effector of RhoA, and peptide-derived ligands that target the p75 neurotrophin receptor upstream of RhoA have also been developed to modulate RhoA/ROCK activity (20). To date, however, there has been a lack of compounds directed at either RhoGEFs or RhoGAPs (28).…”
Section: Discussionmentioning
confidence: 99%
“…The compound was subsequently reported to inhibit Ab-induced cell death in hippocampal, cortical, and septal neurons, decrease activity in a range of toxic/apoptotic signaling pathways, and reverse Ab-mediated neuritic dystrophy and impairment of hippocampal long-term potentiation [33]. Furthermore, LM11A-31 has been shown to inhibit chemotherapeutic agentinduced rhoA signaling [34], and has shown excellent oral absorption, blood-brain barrier penetration and tolerability, and mitigates pathology in models of spinal cord injury and Alzheimer's disease [35,36]. In spinal cord injury, the compound promoted survival of oligodendrocytes, preserved myelin, and improved motor function, and was shown to reduce the interaction of proNGF and p75 NTR in vivo [35].…”
Section: Introductionmentioning
confidence: 99%
“…Platinum agents (cisplatin, oxaliplatin, carboplatin) induce neuronal apoptosis in the DRG through the formation of DNA-platinum complexes and early p38 and ERK1/2 activation. 29,30 Recently, James et al 31 also reported that cisplatin induced neurite degeneration of primary rat neurons in line with the observed axonal neuropathy in patients. Notably, the neurotoxicity of cisplatin can be alleviated by inhibiting the Rho signaling pathway.…”
Section: Chemotherapy-induced Peripheral Neuropathymentioning
confidence: 72%